Less Sacrifice, More Insight: Repeated Low‐Volume Sampling of Microbioreactor Cultivations Enables Accelerated Deep Phenotyping of Microbial Strain Libraries. Issue 9 (19th November 2018) - Hemmerich, Johannes; Tenhaef, Niklas; Steffens, Carmen; Kappelmann, Jannick; Weiske, Marc; Reich, Sebastian J.; Wiechert, Wolfgang; Oldiges, Marco; Noack, Stephan
Abstract : With modern genetic engineering tools, high number of potentially improved production strains can be created in a short time. This results in a bottleneck in the succeeding step of bioprocess development, which can be handled by accelerating quantitative microbial phenotyping. Miniaturization and automation are key technologies to achieve this goal. In this study, a novel workflow for repeated low‐volume sampling of BioLector‐based cultivation setups is presented. Six samples of 20 μL each can be taken automatically from shaken 48‐well microtiter plates without disturbing cell population growth. The volume is sufficient for quantification of substrate and product concentrations by spectrophotometric‐based enzyme assays. From transient concentration data and replicate cultures, valid performance indicators (titers, rates, yields) are determined through process modeling and random error propagation analysis. Practical relevance of the workflow is demonstrated with a set of five genome‐reduced Corynebacterium glutamicum strains that are engineered for Sec‐mediated heterologous cutinase secretion. Quantitative phenotyping of this strain library led to the identification of a strain with a 1.6‐fold increase in cutinase yield. The prophage‐free strain carries combinatorial deletions of three gene clusters (Δ3102‐3111, Δ3263‐3301, and Δ3324‐3345) of which the last two likely contain novel target genes to foster rational engineering of heterologous cutinase secretion in C. glutamicum . Abstract : For accelerated deep phenotyping of microbial strains time‐series data of relevant process variables are required. This study demonstrates a novel workflow that extends the recently introduced Mini Pilot Plant technology and allows determination of classical performance indicators such as titer, rates, and yields from single sub‐mL cultures. The high degree of parallelization without compromising experimental throughput allows rapid and quantitative phenotyping of larger strain libraries, which is of particular importance at the early stages of bioprocess development.